Decoding RNA Editing Sites Through Transcriptome Analysis in Rice Under Alkaline Stress - Rehman, Obaid; Uzair, Muhammad; Chao, Haoyu; Khan, Muhammad Ramzan; Chen, Ming (Frontiers in Plant Science, 2022)
RNA editing (RE) a post-transcriptional process, altered the genetics of RNA which provide the extra level of gene expression through insertion, deletions, and substitutions. In animals it converts the nucleotide residues C-U. Similarly in plants, the role of RES in rice under alkaline stress is not fully studied. Rice is a staple food for most of the world population. Alkaline stress cause reduction in the yield. Here, we explored the effect of alkaline stress on the RES in the whole mRNA from the rice chloroplast and mitochondria. RNA editing sites in both genomes including 345 in chloroplast and 2991 in mitochondria, respectively with average RES efficiency ~55%. Our findings showed that the majority of editing events found in non-synonymous codon changes and change trend in amino acids was hydrophobic. Four types of RNA editing A-G (A-I), C-T (C-U), G-A, and T-C were identified in treated and untreated samples. Overall, RNA editing efficiency was increased in the treated samples. Analysis of GO revealed that the mapped genes were engaged in many biological function and molecular processes. We also checked the expression of PPR, OZ1, and MORF/RIP genes in control and treatment, results revealed upregulation of PPR and OZ1 genes in the treated samples. This induction showed the role of these genes in RNA editing. Current findings report that RNA editing change the amino acids in the edited genes which help the plants to survive in the stressed environments. These findings will provide the basis for identification of RES in other crops and also will be useful in alkaline tolerance development in rice.